A semi-analytical model for energy harvesting of flexural wave propagation on thin plates by piezoelectric composite beam resonators. (15th January 2021) - Wang, Zuowei; Li, Tuanjie
Highlights: A novel plate-harvester consisting of local beam-like oscillators is proposed. A semi-analytical model relating output voltages to incident waves is developed. Multiple scattering is founded to improve harvester efficiency of single oscillator. Abstract: This paper proposed a novel plate-harvester system with local oscillators for energy harvesting of flexural wave propagation. The local oscillator inside a hole was constructed by a piezoelectric composite beam of which two ends were respectively anchored to the host plate and the inner plate. The semi-analytical model of the proposed plate-harvester system was developed by multiple scattering theory of thin plates together with coupled electroelastic dynamics of piezoelectric composite beams. In the multiple scattering modelling, continuous conditions at anchor points of piezoelectric composite beams were used to get the system of linear equations with respect to wave coefficients of displacement fields. The established system of linear equations were solved by a collocation technique. The semi-analytical model was verified by both a T-matrix method and the experiment. Parametric studies were further implemented to analyse the voltage output and normalized energy factor of plate-harvester systems with single and multiple local oscillators. The results demonstrated the feasibility of the proposed plate-harvester system for energy harvesting of flexural wave propagation. Moreover, the harvesting efficiency of single oscillator was well enhanced by multiple scattering of the proposed square arrangement.